2022
DOI: 10.5271/sjweh.4033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in occupational well-being during COVID-19: the impact of age, gender, education, living alone, and telework in a Finnish four-wave population sample

Abstract: Objectives This study investigated how occupational well-being evolved across different phases, before and during the COVID-19 outbreak in the Finnish population. Whereas studies have suggested that certain demographic groups (eg, young, female) are more at risk during COVID-19, less is known whether the effects of such demographic factors may vary (i) across different phases of the unfolding viral outbreak and (ii) on different dimensions of occupational well-being. As they are predictors of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 26 publications
(27 reference statements)
3
24
1
Order By: Relevance
“…Prior to COVID‐19, work engagement remained rather stable over time (for a review, see Mäkikangas, Kinnunen, Feldt & Schaufeli, 2016), as theorized in its definition. Similar findings on stability over time have also been reported during the COVID‐19 pandemic (Kaltiainen & Hakanen, 2022; Oksa et al ., 2021). Some studies have demonstrated a decrease of work engagement during the pandemic (Oksa et al ., 2021; Syrek, Kühnel, Vahle‐Hinz & de Bloom, 2021), but it has also been reported to returned to its prior level when the crisis continued and employees adapted to the new situation and the likelihood that employees psychosocial and physical working conditions changed less (Bernstein, Blunden, Brodsky, Sohn & Waber, 2020; Kaltiainen & Hakanen, 2022).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prior to COVID‐19, work engagement remained rather stable over time (for a review, see Mäkikangas, Kinnunen, Feldt & Schaufeli, 2016), as theorized in its definition. Similar findings on stability over time have also been reported during the COVID‐19 pandemic (Kaltiainen & Hakanen, 2022; Oksa et al ., 2021). Some studies have demonstrated a decrease of work engagement during the pandemic (Oksa et al ., 2021; Syrek, Kühnel, Vahle‐Hinz & de Bloom, 2021), but it has also been reported to returned to its prior level when the crisis continued and employees adapted to the new situation and the likelihood that employees psychosocial and physical working conditions changed less (Bernstein, Blunden, Brodsky, Sohn & Waber, 2020; Kaltiainen & Hakanen, 2022).…”
Section: Introductionsupporting
confidence: 86%
“…Similar findings on stability over time have also been reported during the COVID‐19 pandemic (Kaltiainen & Hakanen, 2022; Oksa et al ., 2021). Some studies have demonstrated a decrease of work engagement during the pandemic (Oksa et al ., 2021; Syrek, Kühnel, Vahle‐Hinz & de Bloom, 2021), but it has also been reported to returned to its prior level when the crisis continued and employees adapted to the new situation and the likelihood that employees psychosocial and physical working conditions changed less (Bernstein, Blunden, Brodsky, Sohn & Waber, 2020; Kaltiainen & Hakanen, 2022). There is also recent evidence that highlighted the within‐person work engagement processes during remote work and yielded altogether four different longitudinal profiles (Mäkikangas et al ., 2022).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of burnout differs by gender among medical professions ( 56 ). Female medical professionals suggested suffer more from burnout, due to discriminative behavior from patients, occupational biases or gendered macro-aggressions ( 57 59 ). However, an investigation assessing the frequency of psychological distress among physician residents showed that, whereas female residents were more likely to suffer from anxiety and depression, male residents were more vulnerable to burnout ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Finland, mental illness is among the top reasons for applying for sickness benefits [ Social Insurance Institution of Finland (SIIOF), 2020 ]. Furthermore, employee ill-being has increased during the COVID-19 pandemic, especially among young adults ( Kaltiainen and Hakanen, 2022 ). Among the young, establishing a career may be challenging ( Vuori and Price, 2015 ) and expectations towards work may be high ( Twenge and Campbell, 2008 ).…”
Section: Introductionmentioning
confidence: 99%